Atorvastatin does not protect against acute myocardial infarction - Barukčić, Ilija (Causation, 2022)
Background: Today, statins are the first-choice agents for reducing high blood cholesterol in people with and without a past history of coronary artery disease (CAD). Methods: Studies which investigated the relationship between statins and coronary events were considered for reanalysis. Results: The contradictions regarding statins are apparent. Some studies show presumed positive effects with respect to coronary events, while other studies do not comply. Conclusion: Statins do not help with the required reliability against coronary events.